Tuo-Min-Ding-Chuan Decoction Alleviates Asthma via Spatial Regulation of Gut Microbiota and Treg Cell Promotion - Yanfei Hong; Zheng Yang; Zirui Liu; Na Li; Jingbo Qin; Dongyu Ge; Guiying Peng; Ji Wang; Qi Wang (Pharmaceuticals)
Objective: Tuo-Min-Ding-Chuan decoction (TMDC), a traditional Chinese prescription, has demonstrated significant clinical efficacy in treating allergic asthma. This study aimed to investigate the mechanism of TMDC in treating asthma from the perspective of Treg cells and gut microbiota across distinct gut segments (jejunum, ileum, cecum, and colon). Methods: An ovalbumin (OVA)-induced asthma model was established in mice, followed by oral administration of TMDC at high, medium, and low dose. Immune cells and lung inflammation were examined to assess asthma severity. Microbial composition was determined by 16S rRNA sequencing. Antibiotic cocktail and Lactobacillus rhamnosus GG (LGG) were administrated to confirm the key role of specific bacteria. Results: TMDC attenuated lung inflammation (p < 0.01) and eosinophilic infiltration (p < 0.01) as well as IL-4 and IL-5 secretion (p < 0.01); it was also associated with an increase in Treg cells in the lung, small intestine (SI), and colon (p < 0.05). Meanwhile, TMDC restored the number of microbiota species and the Shannon index in the hindgut and reinstated beneficial bacteria, such as Allobaculum and Turicibacter, which were diminished in asthmatic mice. Notably, TMDC significantly enriched Bifidobacterium and Lactobacillus, particularly in the hindgut. Lactobacillus abundance was significantly correlated (p < 0.05) with Treg cells, IL-4, IL-5, and eosinophils. Furthermore, LGG supplementation restored elevated lung inflammation (p < 0.05) and decreased Treg cells (p < 0.01) due to antibiotic-induced microbiota depletion. Conclusion: TMDC alleviated asthma by promoting Treg cell expansion in a Lactobacillus-dependent manner across different gut segments, providing new insights into its therapeutic mechanisms.